A dimensão simbólica de escola para crianças - Laêda Bezerra Machado (EccoS – Revista Científica)
This article presents the results of a study whose aim was to capture the social representations of school children at the beginning of schooling. Study participants were 34 children from the 1st cycle of basic education in public schools. As a procedure, was used the kind of conversational interview. Data were organized into thematic categories, according to the guidelines of the analysis of content. The results indicate that children have the following social representations of school: ability to learn to read and write, prepare for the labor market and, consequently, social ascension. The proposal Moscovician is therefore strengthened by the fact that for this group the school has a mesh of senses and meanings, engendered in their social environment, which works as a guide to action.